2015 Best Paper Award: Analysis method of ultimate hull girder strength under combined loads. (2nd April 2016) - Tanaka, Yoshiteru; Ogawa, Hiroaki; Tatsumi, Akira; Fujikubo, Masahiko
Abstract : The objective of this study is to propose an analysis method of ultimate hull girder strength under combined bending and torsion. The hull girder is modelled by a series of thin-walled linear beam elements composed of plate and stiffened panel elements and their average stress–average strain relationships under axial loads considering the effect of shear stress are implemented in the beam elements. First, torsional moment is applied to the beam model as a whole model within the elastic range. Then, the ultimate bending strength of cross sections is calculated applying the Smith's method to beam elements considering the warping and shear stresses. The proposed simplified method is applied to the progressive collapse tests of scale models under combined loads. On the other hand, nonlinear explicit finite element method (FEM) is adopted for the analysis of the test models. The effectiveness of the proposed method is discussed comparing with the results of experiments and FEM analysis.